BUILDING CONSUMER LOYALTY: WHY GENDER DIFFERENCES MATTER FOR NIKE IN BANDUNG? - Jalilah, Ida; Susilawati, Lena (Harmoni Ekonomi Multidisiplin, 2024)
Background: Consumer loyalty is a critical factor for the long-term success of a brand, driving profitability, customer retention, and brand advocacy. Nike, as a global brand, faces increasing competition, especially from newer brands such as On and Hoka, which affects their fiscal revenue forecast. This study aims to examine the differences in loyalty between male and female consumers in Bandung towards the Nike brand, focusing on the influence of gender in shaping brand loyalty. Methods: This study used a descriptive approach and independent t-test to identify gender-based loyalty differences. Data was collected through a survey of male and female consumers who use Nike products in Bandung. The responses obtained were analyzed to determine the variability of loyalty between the two groups, with loyalty factors such as product satisfaction, emotional attachment, and brand preference. Results: The results show that male consumers have higher loyalty to the Nike brand than females. Independent t-tests confirmed a significant difference in loyalty levels between genders, with p-values below 0.05. These findings are in line with previous research showing that male consumers tend to form stronger brand loyalty through emotional attachment and product satisfaction, whereas female consumers show more variability in brand preference. Keywords: Consumer loyalty, Gender differences, Consumer behavior, Nike, t-test